Greenhouse Gas Emissions from Soils are Affected by Irrigation Water Sources - TAO Zhen; LI Zhongyang; LI Songjing; LI Baogui; LI Siyi; GAO Feng; LIU Yuan (Guan'gai paishui xuebao, 2022)
【Objective】 Reducing greenhouse gas (GHG) emissions from soils play an important role in controlling the temperature rise not exceeding 1.5 ℃ by the end of the century. GHG emission is complicated, affected by various physical and biogeochemical processes. In this paper, we studied the impact of irrigation water sources on emissions of CO2, N2O, and CH4 from soils. 【Method】 Incubation experiment was conducted indoors in microcosms. The microcosms were irrigated using reclaimed wastewater, livestock wastewater respectively, with irrigation with fresh groundwater taken as the control. During the experiment, we measured, concurrently, the emissions of CO2, N2O and CH4, the changes in soil pH, water-filled porosity (WFPS), NH4+-N and NO3--N, as well as other edaphic factors. 【Result】 Reclaimed water and livestock wastewater irrigations both significantly increased the emission of CO2, N2O and CH4, compared to irrigation with groundwater (P<0.05). In particular, it was found that reclaimed water irrigation increased N2O emission most, while livestock wastewater irrigation respired more CO2 and CH4 compared to other treatments. In terms of global warming potential (GWP), there was no significant difference in GWP between the reclaimed water irrigation and the livestock wastewater irrigation; however, compared to groundwater irrigation, they both significantly increased GWP (P<0.05). Compared to the control, the livestock wastewater irrigation reduced soil pH, while the reclaimed water irrigation increased soil pH, both at significant levels. Nitrogen in soil irrigated with groundwater was lower than that irrigated by the reclaimed and livestock wastewaters. 【Conclusion】 In terms of GWP and change in soil properties, reclaimed wastewater and livestock wastewater irrigation increased GHG emissions and enhanced mineral nitrogen in soil.